Cultural conceptions about mental health of people on psychological therapeutic process - Torres López, Teresa Margarita; Munguía Cortés, Jazmín Aranzazú; Salazar Estrada, José Guadalupe; Aranda Beltrán, Carolina (Actualidades en Psicología, 2015)
The objective was to analyze mental health cultural conceptions’ of adult people with experiences on psychological therapeutic process from Guadalajara, Mexico. Method: 77 persons selected by purposive sampling were interviewed. It was applied free listing and pile sort technics. The analysis was by consensus, hierarchical cluster and multidimensional scaling. The participants’ conceptualized mental health like the well-being, health and sanity obtained by the professional and institutions health support. For them, mental health is the balance, tranquility, pace, harmony, love, happiness, plenitude, enthusiasm, confidence and agreement. In other hand, lack of mental health would be generating some mental illness (neurosis, psychosis, depression). The results showed genre differences and high woman consensus than the men, that allowed suggest differential basis for design promoting programs of mental health.